STRATEGISING FOR RURAL INDIA: A LITERATURE-BASED THREE-PRONGED CONCEPTUAL MODEL - Patra, Purnendu Kumar; Agarwal, K K (The journal of contemporary issues in business and government, 2021)
Strategy, as regards business, is a long term course of action to fulfill objectives. Organizations make long term plans to achieve their ends using means available to them internally and in the environment. All strategies tend to result in the firm achieving more than what a competitor achieves or lose less than what others do. Villages of India lack basic infrastructure, are agriculturally rich, are opposed to English language and practically to any fruitful activity contributing to economic growth. More than half of India lives in its villages which don’t even have access to basic life essentials like health, education, access and clean fuel. This set of challenges calls for a pragmatic approach in strategising for rural India. A review of literature was undertaken which revealed three, not very distinct, bodies of work covering the aspects of Marketing, Ethics and Innovation in strategy making. A conceptual plan was derived out of the study calling for an integration of all three aspects which has been posited to make Rural Marketing strategy a success. Gaps in research have been pointed out and recommendations made.